Ansari’s method in generalizations of some results in the fixed point theory: Survey - Došenović, Tatjana M.; Radenović, Stojan N. (Vojnotehnički glasnik / Military Technical Courier, 2017)
The aim of this paper is to show that the C-class function introduced by A. H. Ansari is a powerful weapon for the generalization of many important results in the theory of fixed points.